Evaluation of different 4x4 Coded MIMO System - Qaradaghi, Thuraya Mahmood; Hussein, Diana Hayder (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper 4x4 coded MIMO-OFDM systems with two different code rate OSTBC (1/2 and 3/4) and different types of QAM as a baseband modulation have been studied, and compared with a 4x2 coded MIMO system. The system has been evaluated over a multipath flat-fading and frequency-selective fading, assuming channels with non line of sight (NLOS). Three different Doppler frequencies (5, 50 and 100 Hz) have been used to study the systems in different channel situations. The results shows that increasing the number of antennas at the receiver side reduce the effect of the Doppler shift, because increasing the number of antennas means increasing the number of channels, and transmitting the symbols through these channels in different times. OSTBC with two different code rate (R=1/2 and 3/4) have been used with 4 transmitting antennas, and OSTBC with R= 1/2 gives a better results than the one with R= 3/4, because when R=3/4 three symbols are send during 4 time slots, but when R=1/2 just two symbols are send during four time slots. That is beside sending multi-copies of each symbol in different time and different space
Keywords: MIMO; OFDM; OSTBC; Rayleigh Channel